2011
DOI: 10.1016/j.vaccine.2011.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hepatitis B vaccine responses during chronic hepatitis C infection: Involvement of the PD-1 pathway in regulating CD4+ T cell responses

Abstract: Vaccination for hepatitis B virus (HBV) in the setting of hepatitis C virus (HCV) infection is recommended, but responses to vaccination are blunted when compared to uninfected populations. The mechanism for this failure of immune response in HCV-infected subjects remains unknown but is thought to be a result of lymphocyte dysfunction during chronic viral infection. We have recently demonstrated that PD-1, a novel negative immunomodulator for T cell receptor (TCR) signaling, is involved in T and B lymphocyte d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 39 publications
4
65
0
2
Order By: Relevance
“…Using NP co-immunization, our model recapitulates the diminished response against a secondary antigen and elucidates the role played by IFN-I-mediated signaling in the chronic infection setting. Other studies have also shown that poor responses against vaccines are correlated with an increased PD-1:PD-L1 profile in HIV and HCV infected patients (10, 52). …”
Section: Discussionmentioning
confidence: 94%
“…Using NP co-immunization, our model recapitulates the diminished response against a secondary antigen and elucidates the role played by IFN-I-mediated signaling in the chronic infection setting. Other studies have also shown that poor responses against vaccines are correlated with an increased PD-1:PD-L1 profile in HIV and HCV infected patients (10, 52). …”
Section: Discussionmentioning
confidence: 94%
“…This could explain in part why HCV-positives have lower response rates to hepatitis B virus (HBV) vaccination. 38 However, this hypothesis assumes that it is in fact individuals with naïve T-cell lymphopenia that respond less well to HBV vaccination, which would need to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with observations in LCMV 74,75 . In addition, humoral responses against other antigens might be compromised in patients with chronic HCV; specifically, one study noted that antibody responses against hepatitis B vaccination were lower in individuals with chronic HCV than in uninfected individuals 99 . This observation suggested that Tfh:B cell dysfunctional interactions might be due, at least in part, to a putative bystander effect from surrounding inflammation, although this has not been directly tested.…”
Section: Cd4+ T Cells In Human and Non-human Primate Chronic Viral Inmentioning
confidence: 99%